Maternity, metrics and morale: Addressing the continued attrition of women from science - Cameron, Elissa; White, Angela; Gray, Meeghan (New Zealand Science Review, 2014)
​Women continue to be under-represented in science careers globally, despite decades of awareness of gender issues in STEM§ (Shen 2013, Larivière et al. 2013). While in some fields, women are under-represented at all career stages, in other fields (particularly biological sciences) an increasing number of women are attracted into undergraduate programmes (O’Brien & Hapgood 2012, Moss-Racusin et al. 2012). However, even in fields in which women outnumber men in undergraduate pro-grammes (like ecology, Martin 2012), women are increasingly under-represented with advancing career stage, suggesting either a glass ceiling preventing career advancement (e.g. Dobele et al. 2014), or a leaky pipeline effect, whereby more women than men leave science without career advancement (e.g. Pell 1996). These factors suggest a very different experience of the science career environment by men and women.